A study on the formation process of the two characters '䉼, 剬' shown in Kehong yinyi 可洪音义. (June 2019) - Lee, Kyoo-Kap
Although the two characters '䉼, 剬' appearing in Kehong yinyi are originally regular scripts by themselves, they are used as variant forms of the characters '料' and '制', respectively, in this book. As such, the character shapes of variant forms appear the same as the regular scripts of other characters in many cases. This paper describes how these variant forms are made.